Global analysis of an exponential model of cell proliferation for estimation of cell cycle duration in the root apical meristem of angiosperms. (7th February 2018) - Zhukovskaya, Natalia V; Bystrova, Elena I; Dubrovsky, Joseph G; Ivanov, Victor B
Abstract: Background and Aims: Information on cell cycle duration ( T ) in the root apical meristem (RAM) provides insight into root growth, development and evolution. We have previously proposed a simple method for evaluating T based on the dynamics of root growth ( V ), the number of cells in the RAM ( Nm ) and the length of fully elongated cells ( l ), which we named the rate-of-cell-production (RCP) method. Here, a global analysis was performed to confirm the reliability of this method in a range of angiosperm species and to assess the advantages of this approach. Methods: We measured V, Nm and l from live or fixed cleared primary roots of seedlings or adventitious roots of bulbs and used this information to estimate the average T values in 73 angiosperm species via the RCP method. The results were then compared with published data obtained using the classical but laborious and time-consuming 3 H-thymidine method. Key Results: In most species examined, the T values obtained by the RCP method were nearly identical to those obtained by the 3 H-thymidine method. Conclusions: The global analysis demonstrated that the relationship between the variables V, Nm and l in roots in the steady state of growth is correctly described by the equation T = (ln2 Nm l ) V −1 . Thus, the RCP method enables cell cycle duration in the RAM to be rapidly and accurately determined. This method can be performed using live or fixed roots for each individual cell type. The simplicity of the approach suggests that it will be widely used in phenomics, evolutionary ecology and other plant biology studies.